Eksistensi dan Karakteristik Batik Motif Warak Ngendog di Kampung Batik Semarang dalam Era Modern - Alifah Rahmawati; Afrizal Afrizal (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2023)
The background of this research is to describe in depth the existence and characteristics of Warak Ngendog motif batik in Semarang batik village. Batik is one of Indonesia's cultural heritages which has been recognized by UNESCO as Masterpieces of the Oral and Intangible Heritage of Humanity. This research is a type of qualitative research with a descriptive interpretative presentation and uses an aesthetic approach, namely aesthetics according to A.A.M Djelantik's theory, used to describe the existence and characteristics of the Warak Ngendog batik motif in Semarang batik village. Therefore, this study aims to determine the existence and characteristics of the Warak Ngendog batik motif in Semarang batik village in the modern era. The results showed that the existence of the Warak Ngendog motif batik in Semarang batik village was still maintained, although there were several challenges that had to be faced. The characteristics of the Warak Ngendog batik motif in Semarang batik village consist of aspects of shape, color, and aesthetic value that are still maintained according to their origins. However, there are also adaptations to market demand that affect the choice of motifs and colors.